Analyzing Student Follow-up and Feedback in Medical School Classroom Discussions - Lemus Amescua, Elsy Valeria (2021)
Follow-up and feedback are an important part of classroom discussions and are frequently used by instructors to provide information to students regarding their knowledge as well as develop new learning skills. This study identifies interactions among the instructor, student speakers and students at large using the IRE/F structure and how, through follow-up and feedback, student leverage on this opportunity to play active roles as participants, while they rebuild and reflect on their knowledge. Study participants included three instructors at the FES Iztacala Medical School at the Autonomous University of Mexico (UNAM) and their students. Classes were recorded, transcribed and encoded using MAXQDA20 software and then transferred to SDIS-GSEQ. The results of the study reveal that students played a more passive role as learners during certain discursive sequences, while, at other times, they were more engaged and participate actively. It was concluded that students successfully used feedback and follow-up to gain insight and expand, emphasize, confirm or add to classroom discussion.